Analisis Faktor-Faktor Yang Mempengaruhi Pemilihan Lokasi Industri Amplang di Kota Samarinda - Adli Lazuardi; Bambang Indratno Gunawan; Elly Purnamasari (2339-1324, 2021)
This research aims to determine respondents perceptions of the factors of location costs, population, and proximity of consumers in the selection of industrial locations in the city of Samarinda and identify obstacles in the selection of industrial locations in the city of Samarinda. This research was conducted for 7 months starting in August 2019 until February 2020. The sample method used was purposive sampling with a sample taken of 20 respondents. The analytical method used is multiple linear regression analysis. The results of this study indicate that location costs (X1), population (X2) and consumer proximity (X3) have a joint (simultaneous) effect on the selection of location (Y) of the envelope industry in Samarinda City with model = 0.451 X1 + 0.486 X2 + 0.061 X3, then the cost of location (X1) and population (X2) partially influences location selection (Y), while consumer proximity (X3) has no partial effect on location selection (Y). The location selection constraints experienced by amplang producers in Samarinda City are the high location costs, the increase in the cost of renting a place each year, and accessibility. Keywords: Location Cost, Population, Consumer Proximity, Location Selection and Amplang Industry.